2015
DOI: 10.1007/s11657-015-0231-6
|View full text |Cite
|
Sign up to set email alerts
|

Compliance and persistence with daily, weekly, and monthly bisphosphonates for osteoporosis in Japan: analysis of data from the CISA

Abstract: SummaryCompliance and persistence with daily, weekly, and monthly bisphosphonates (BPs) for osteoporosis were assessed using data from the Platform for Clinical Information Statistical Analysis (CISA) database that contains data of prescriptions in 13 university hospitals in Japan. The analysis revealed compliance and persistence improved as the dosing interval increases.PurposeBPs are an effective first-line therapy for osteoporosis, but adherence is low. Compliance (medication possession ratio, MPR) and pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 30 publications
3
58
0
3
Order By: Relevance
“…Furthermore, compliance was higher with monthly than with daily therapies. In line with these findings, Kishimoto and Maehara showed that a monthly regimen has better treatment compliance when compared with weekly and daily regimens 18. These results suggest that compliance and potential convenience are inversely related to the administration frequency of a given treatment.…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, compliance was higher with monthly than with daily therapies. In line with these findings, Kishimoto and Maehara showed that a monthly regimen has better treatment compliance when compared with weekly and daily regimens 18. These results suggest that compliance and potential convenience are inversely related to the administration frequency of a given treatment.…”
Section: Discussionmentioning
confidence: 61%
“…As a result, we found that zoledronic acid might be costeffective compared to alendronate if zoledronic acid was expected to improve the proportion of patients who continued treatment for over a year by 10% compared to alendronate with a few exceptions. Recently, Kishimoto and Maehara reported that the 1 year medication possession ratio (MPR), which was used as an indicator of compliance, was 70.6% for weekly oral bisphosphonates in Japan [43]. If we assumed the proportion of patients who continued therapy for over a year in alendronate arm was equal to 70% based on the previous report, the costeffective threshold for the proportion of treatment persistence for over a year in zoledronic acid arm was estimated to be about 80% or more.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers who received monthly vitamin D supplementation in the reviewed studies were administered their dose on-site; mothers who received daily supplementation were largely responsible for their own administration. An unrelated study in Japan found that monthly dosing of bisphosphonates for osteoporosis had higher compliance compared to daily and weekly dosing [18]. Additional studies assessing compliance in relation to maternal self-administered vitamin D supplementation need to be conducted to confirm these results.…”
Section: Discussionmentioning
confidence: 99%